2020
DOI: 10.1364/prj.380249
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-to-microwave room-temperature photodetectors based on three-dimensional graphene foams

Abstract: Highly sensitive broadband photodetection is of critical importance for many applications. However, it is a great challenge to realize broadband photodetection by using a single device. Here we report photodetectors (PDs) based on three-dimensional (3D) graphene foam (GF) photodiodes with asymmetric electrodes, which show an ultra-broadband photoresponse from ultraviolet to microwave for wavelengths ranging from 10 2 to 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…In addition, the R and NEP curves present a linear relationship with the power, which is consistent with the previous reported results. 3 Fig. 3c shows the optical switched on/off photocurrents of the device under 2.52 THz irradiation with varying power intensities at 0 V bias voltage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the R and NEP curves present a linear relationship with the power, which is consistent with the previous reported results. 3 Fig. 3c shows the optical switched on/off photocurrents of the device under 2.52 THz irradiation with varying power intensities at 0 V bias voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Broadband photodetectors (PDs) that offer operation over the range from the near infrared (NIR) to terahertz (THz) region in a single device with simple structures are promising for applications including imaging, remote sensing, communications and spectroscopy. [1][2][3] In particular, with the continuing development of THz technology, self-powered, fast response and room temperature THz PDs are urgently required for space network communication and biomedical imaging. [4][5][6] However, the current commercial detectors can hardly meet these requirements; for example, the detection range of Ge photodiodes is limited to 400-2000 nm, the Bolometer must work at low temperature (1.5-4.2 K), Golay cells always show a slow response time of about 100 ms and Schottky diodes can only detect frequency below 0.33 GHz.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have investigated a graphene-based pyroelectric bolometer for detecting the warm bodies in their proximity 38 , and a pyroelectric infrared (IR) sensor with graphene electrodes can improve the operating frequency instead of conventional electrode 39 . Recently, some researchers have reported that graphene-based terahertz photodetectors, whose performance can be dramatically improved by photo-thermoelectric effect (PTE) 41,42 . However, there are few studies on multifunctional self-powered photodetector which can detect and distinguish light energy and heat energy at the same time.…”
mentioning
confidence: 99%